Implementasi Program Kartu Keluarga Sejahtera dalam Meningkatkan Kesejahteraan Masyarakat Kelurahan Wonokusumo Kota Surabaya - Aditya Saputra, Septian; Azhari, Salsabillah; Jannah, Miftakhul; Septriana Munthe, Gratia Uli; Pertiwi, Vidya Imanuari (VISA: Journal of Vision and Ideas, 2024)
The success of development carried out by a country can be seen from the existence of its poor people. To improve community welfare, the Surabaya city government implemented a program provided by the Ministry of Social Affairs, namely the Prosperous Family Card Program. The purpose of carrying out this research is to see whether the implementation of the Prosperous Family Card Program in Wonokusumo Subdistrict the poorest subdistrict in Surabaya has gone well by George Edwards III's theory which is based on empathy and uncertainty, namely bureaucratic structure, disposition, resources and communication. This research uses qualitative methods with a phenomenological perspective with primary data sources and secondary data sources. The results of the research show that Wonokusumo Village has implemented the program optimally, where there has been good coordination between the parties involved and the tasks carried out are by applicable regulations. Likewise, Wonokusumo Village has carried out its function as a distributor of assistance for the Prosperous Family Card Program and as an organizer of socialization of the program so that it becomes better known to the public.